Strategi Pelestarian Ngaji Tematik dan Fikih Klasik di Ruang Digital untuk Menjawab Tantangan Global - Muchammad Lubbil Khobir Lubbil; Solchan Ghozali (Jurnal Riset Pendidikan Multidisiplin dan Pengabdian Kepada Masyarakat, 2025)
In the era of globalisation, the tradition of thematic Qur'anic study (ngaji tematik) and classical fiqh face significant challenges, including the erosion of traditional learning spaces and competition from fragmented religious content. However, digital technology offers unprecedented opportunities to democratise access to classical Islamic knowledge (al-turats al-Islami), while preserving its authenticity and depth. This community service programme (PkM) aims to design and implement a digital learning model using Google Meet to preserve thematic Qur'anic study and classical fiqh. The programme will also analyse the impact of this approach on reaching wider audiences and evaluate the challenges involved in building a participatory digital learning community. The study employed Participatory Action Research (PAR), involving 75 participants from diverse backgrounds over a period of six months. Data were collected through participatory observation, in-depth interviews and an analysis of documents from 16 learning sessions. Qualitative data were analysed using thematic analysis to identify key patterns and insights. The programme successfully developed a three-phase implementation strategy (planning, action and reflection) that effectively created an inclusive digital learning space. Key findings include: (1) the significant democratisation of access to classical Islamic studies across geographical boundaries; (2) the successful adaptation of traditional pedagogical methods (bandongan) through digital, interactive features; and (3) the formation of a cohesive digital community that maintained the values of ukhuwah (brotherhood) and knowledge transfer (naql al-‘ilm). A SWOT analysis revealed that, with proper pedagogical adaptation and community building, digital platforms can serve as effective sanctuaries for preserving classical Islamic knowledge. The Google Meet-based learning model is effective in addressing globalisation challenges by combining technological flexibility with the preservation of the essence of traditional Islamic scholarship. This approach offers a sustainable way to maintain classical learning traditions and expand their reach to modern audiences, making a significant contribution to the discourse on the digitalisation of religious education.